2020
DOI: 10.1186/s12916-020-01719-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical features of pediatric COVID-19

Abstract: Background: COVID-19 is an extremely severe infectious disease. However, few studies have focused on the epidemiological and clinical characteristics of pediatric COVID-19. This study conducted a retrospective review of the epidemiological and clinical features of COVID-19 in children. Methods: A retrospective study was conducted on children with a definite diagnosis of COVID-19 in mainland China using the web crawler technique to collect anonymous COVID-19 updates published by local health authorities. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
138
3
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(186 citation statements)
references
References 15 publications
21
138
3
10
Order By: Relevance
“…In addition, 26% of pediatric cases showed normal chest radiological imaging on admission, which also makes it difficult to identify the suspected cases. Consistent with the findings of Guo et al (20), our results revealed that the pooled mean incubation period in children was 9.57 days, which was longer than adults (4 days) (21). This might be explained by children being less likely to be tested for coronavirus infection due to the proxy reports of symptoms in younger children, especially at pre-school age.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, 26% of pediatric cases showed normal chest radiological imaging on admission, which also makes it difficult to identify the suspected cases. Consistent with the findings of Guo et al (20), our results revealed that the pooled mean incubation period in children was 9.57 days, which was longer than adults (4 days) (21). This might be explained by children being less likely to be tested for coronavirus infection due to the proxy reports of symptoms in younger children, especially at pre-school age.…”
Section: Discussionsupporting
confidence: 91%
“…9 A recent study highlighted that the main form of COVID-19 infection in children (4 days to 14 years old) was through family groups, and that standing out among the clinical characteristics were long incubation periods, fever and coughing. 16 The same study found that 30% of asymptomatic children had post-infection lung damage. 16 Although hospital lethality was greater among children under 1 year old, they were closely followed by adolescents aged 15-19 years old.…”
Section: Discussionmentioning
confidence: 92%
“…16 The same study found that 30% of asymptomatic children had post-infection lung damage. 16 Although hospital lethality was greater among children under 1 year old, they were closely followed by adolescents aged 15-19 years old. It is possible that among adolescents hospitalized with COVID-19, pre-existing chronic conditions may have been associated with worsening of the clinical picture and with high death and lethality frequency in the group studied.…”
Section: Discussionmentioning
confidence: 92%
“…Although limited data in the literature regarding the vertical transmission of the SARS-CoV-2 from infected pregnant mother to the fetus are available, some epidemiological studies in this context concluded that this means of transmission is unlikely to exist (42,43). As per the virus source to the children, another comprehensive study included a considerable number of Chinese children with definite COVID-19 indicated that most of them acquired the infection from the familial sources (69). As a general important epidemiological note, the sources and transmission modes of the virus for pediatric COVID-19 is considered extremely important for understanding the role of children in the dynamics of the pandemic as they may become a sizable factor in the disease spread in many parts of the world (70).…”
Section: Infection Acquisitionmentioning
confidence: 99%
“…The incubation period of COVID-19 in pediatric patients was appraised and discussed in several studies. It had been estimated as 5-6 days in some reports (43, 51) and 9-11 days in others (9,52,69). An overwhelming data retrieved from the literature revealed that the asymptomatic nature of COVID-19 among many infected children worldwide was observed (55)(56)(57).…”
Section: Clinical Manifestationsmentioning
confidence: 99%